Organic fertilizer produced from chicken carcasses on soybean production - Willian Melo; Natalia Pereira; Edna de Andrade; Reginaldo Santos; Luiz Zanão Júnior (International Journal of Recycling of Organic Waste in Agriculture)
Purpose The objective of this study was to evaluate soybean production and nutrient availability in the soil using doses of organic fertilizer formed from chicken carcasses, compared to the use of mineral fertilizer.Method The evaluated treatments, produced from chicken carcasses, were calculated to provide 0, 30, 60, 90, 120 kg ha-1 of P2O5, that is, 0; 3.37; 6.71; 10.11 and 13.48 t ha-1, respectively. We also evaluated an additional treatment, in which 60 kg ha-1 of P2O5 were applied, through 400 kg ha-1 of NPK 10-15-15; this was carried out in a rural area located in the municipality of Ubiratã, Western Paraná. After harvest, the plant production components of soybean were evaluated, as well as the P content in the soil. The data were submitted to analysis of variance (ANOVA). The effect of the organic compost doses was evaluated by regression analysis and the additional treatment was compared by contrast analysis.Results The use of organic compost doses based on chicken carcass in soybean cultivation resulted in linear increase in plant height, number of pods per plant, thousand grain weight productivity and oil content in the grains. It was also efficient in increasing P levels of the soil. Compared to mineral fertilizer, the use of organic compost resulted in greater amount of P available in the soil but had a lower productivity.Conclusion Organic fertilizer from chicken carcass was able to increase the production components of soybean as well as to increase the soil P availability.